Investigation of structural, kinetics and electrical properties of CuAlMnZn shape memory alloy – p-type silicon Schottky diode - Aldirmaz, E.; Güler, M.; Güler, E.; Dere, A.; Tataroglu, A.; Yakuphanoğlu, Fahrettin (Elsevier B.V., 2021)
SEM (scanning electron microscopy) and DSC (differential scanning calorimetry) measurements were done to characterize the microstructure and transformation temperature properties of the materials. The CuAlMnZn shape memory alloy (SMA) was used as a Schottky contact in Schottky diode fabricating. The electrical behavior of the diode was investigated using current and admittance experiments. Current-voltage (I–V), capacitance-voltage (C–V) and conductivity voltage (G/?-V) measurements of the produced diode were carried out at room temperature, dark, light and at different frequencies. For the diode we obtained, basic diode parameters such as ideality factor (n), barrier height (?b), shunt resistance (Rsh) and series resistance (Rs) were calculated. The current-voltage (I–V) measurements showed that the produced diode exhibits a good rectification in dark conditions. The frequency and potential dependence of the C–V and G/?-V characteristics of this diod were investigated. It was observed that the C–V and G/?-V characteristics changed significantly with frequency. The increase in capacitance, especially at low frequencies, was attributed to the presence of interfacial states at the metal/semiconductor interface. The Rsh and Rs values were observed to decrease with illumination. The experimental observations showed that the CuAlMnZn/p-Si Schottky diode can be used as a photodiode for optoelectronic applications. © 2021
Keywords: CuAlMnZn alloy; DSC; Electrical properties; Metal-semiconductor contacts